Mediation of socioeconomic inequalities in preterm birth. A cohort analysis of Welsh linked data - Philip McHale; Daniela K. Schlüter; Hoda Abbasizanjani; Ashley Akbari; Ben Barr; David Taylor‐Robinson (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Consistent socioeconomic inequalities in preterm birth prevalence are seen internationally. Understanding the pathways to inequalities in preterm birth and the mediators that contribute to these inequalities is essential to inform policies and interventions to reduce health inequalities across the life course. Material and Methods We conducted a causal mediation analysis using routinely collected, anonymised population‐scale, individual‐level linked data within the SAIL Databank on all singleton live births in Wales between 1 January, 2000 and 30 September, 2019. Our outcome was preterm birth, and exposure was area‐based deprivation. Mediators were smoking during pregnancy, maternal mental health, hospitalisation due to maternal physical health and obstetric conditions. We calculated inequalities in preterm birth (dichotomised as before or after 37 weeks) and estimated two measures of mediation: proportion eliminated, the percentage of the effect of deprivation on preterm birth eliminated by removing the mediators, through the Controlled Direct Effects; and proportion mediated, the percentage of the inequality removed by equalising the distribution of the mediators across socioeconomic strata. Multiple multivariate imputations by chained equations were used to deal with missing data. Results The final sample included 609 610 live births with 6.1% preterm. Socioeconomic gradients were seen in preterm birth and exposure to mediators, with a higher occurrence in mothers residing in the most compared to the least deprived quintiles. Compared with the least deprived quintile, the odds ratio for preterm births in the most deprived quintile was 1.26 (95% confidence interval 1.22–1.31). The proportion eliminated by the removal of all mediators at the same time was 21%. The proportion mediated by maternal smoking during pregnancy was 26%, and less than 10% for other mediators. Discussion Smoking during pregnancy is a significant mediator of preterm birth inequalities. Maternal mental and physical health during pregnancy and obstetric conditions also lie on the pathway from socioeconomic status to preterm birth but mediate the relationship to a lesser extent. Significant socioeconomic inequalities remained after the effect of mediators was removed. These findings suggest that there is a need to reduce inequalities in smoking during pregnancy and direct action on socioeconomic status during pregnancy.